Expression of biomarkers related to cell adhesion, metastasis and invasion of breast cancer cell lines of different molecular subtype - Chekhun, S.; Bezdenezhnykh, N.; Shvets, J.; Lukianova, N. (Experimental Oncology, 2013)
Aim:The aim of our study was to determine the complex of molecular genetic markers which are associated with cancer aggressiveness, invasion and metastasis among different molecular subtypes of breast cancer cell lines. Materials and Methods: The cell lines used in the analysis include T47D, MCF-7, MDA-MB-231, MDA-MB-468, MCF-10A and 184A1. Expression of estrogen receptor, progesterone receptor, Her-2/neu and Ki-67 was studied by immunocytochemical method. CD24, CD44 and E-cadherin expression was studied by flow cytometry. Results: We have identified biomarkers which characterize metastatic potential of human breast cancer cells of certain molecular subtypes. It has been demonstrated that low colony forming activity of human breast cancer cells of luminal subtype is accompanied by increased adhesive properties of these cells due to high level of E-cadherin expression, low level of CD44 expression and absence of CD24 expression. High tumorigenicity of cells of basal subtype is connected to weakening of adhesive contacts that is caused by abnormalities of E-cadherin expression, significant increase of CD44 expression and presence of low level of CD24 expression. Conclusion: Our data indicated that changes of correlation between expression of cellular adhesion molecules inside conventional immunohistochemical subtypes reflect significantly wider biological properties of luminal and basal subtypes of human breast cancer.